2008
DOI: 10.1007/s00005-008-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between impaired apoptosis of lymphocytes and distribution of dendritic cells in peripheral blood and synovial fluid of children with juvenile idiopathic arthritis

Abstract: Introduction: The pathogenesis of juvenile idiopathic arthritis (JIA) is not fully understood. Recently the present authors described disturbed apoptosis of JIA lymphocytes in both peripheral blood (PB) and synovial fluid (SF) as well as an abnormal distribution of blood dendritic cells (BDCs) between the PB and SF in this disease. Possible relationships between these events during the development of JIA process are assessed here. Materials and Methods: Lymphocyte apoptosis and BDC counts were assessed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In their synovial fluid we find around 5-10 Â 10 6 cells per ml with 1.2e2.4 Â 10 6 CD4þ cells per milliliter and 1.6-3.2 Â 10 6 CD8þ cells per milliliter. This is a little bit lower for CD4þ T-cells but the same for CD8þ cells as has been published before by others who calculated that synovial fluid of their JIA patients contains a median of 8.5 Â 10 6 CD4þ T-cells and 2.4 Â 10 6 CD8þ cells per millilitre [45]. In the synovial fluid (SF) of arthritic knees from 14 JIA patients we found mesenchymal stromal cells at a low rate: a median of 4 CFU-F per million SF cells with a maximum of 81 CFU-F. On the contrary normal (healthy) SF was reported to have 250 CFU-F per 1 million SF cells [7].…”
Section: Presence Of Msc In the Jointsupporting
confidence: 53%
“…In their synovial fluid we find around 5-10 Â 10 6 cells per ml with 1.2e2.4 Â 10 6 CD4þ cells per milliliter and 1.6-3.2 Â 10 6 CD8þ cells per milliliter. This is a little bit lower for CD4þ T-cells but the same for CD8þ cells as has been published before by others who calculated that synovial fluid of their JIA patients contains a median of 8.5 Â 10 6 CD4þ T-cells and 2.4 Â 10 6 CD8þ cells per millilitre [45]. In the synovial fluid (SF) of arthritic knees from 14 JIA patients we found mesenchymal stromal cells at a low rate: a median of 4 CFU-F per million SF cells with a maximum of 81 CFU-F. On the contrary normal (healthy) SF was reported to have 250 CFU-F per 1 million SF cells [7].…”
Section: Presence Of Msc In the Jointsupporting
confidence: 53%
“…This is of interest, given the different patterns of expression of the 2 isoforms, as initially demonstrated in mice by He, et al 32 . The finding of increased RORC2 expression in SF might partly explain the impaired resistance to apoptosis seen in SF lymphocytes of JIA patients 43,44 since RORγt, the equivalent of RORC2 in mice, was shown to protect T cells from activation-induced cell death 32 . An antagonistic immune response between Treg and Th17 in situ in the joints of patients with JIA is in line with recent findings showing that Treg and Th17 cells are reciprocally regulated during differentiation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has confirmed the presence of cells expressing CD1a or CD83 in the synovial tissue of patients with arthritis [9,10,29,30]. Smolewska et al confirmed expression of C83 on CD1c positive dendritic cells in the synovial fluid of JIA patients [17]. The CD83 molecule could be important not only when expressed on the cell surface, but also in soluble form.…”
Section: Hla-dr Positive Cells In Blood and Synovial Fluidmentioning
confidence: 61%